Vers un modèle pédagogique de compréhension des textes - Karpińska-Szaj, Katarzyna (Studia Romanica Posnaniensia, 2003)
The interactive reading model deals with the capacity for reading in terms of text reception in a native language. In the article, we try to place the interactive reading model in the foreign language learning/teaching situation, assuming that mental operations carried out by a foreign language reader learner can be described as strategies of understanding. By showing the specific nature of such strategies and distinguishing a superior strategy (the one that controls the use of the others), we attempt to build a didactic model of text reception in a foreign language.